FECAL CALPROTECTIN AS A MARKER OF INFLAMMATION IN THE COLON AT DIFFERENT VARIANTS OF CLOSTRIDIUM DIFFICILE-INFECTIONS COURSE IN CHILDREN - L. N. Mazankova; S. G. Gorbunov; B. Yunes (LLC "Diagnostics and Vaccines", 2015)
The article discusses possible application of determination of the fecal calprotectin level in children with antibiotic-associated diarrhea caused by Clostridium difficile - infection to detect inflammation in various parts of the gastrointestinal tract. It is shown that calprotectin is an informative non-invasive method that can estimate the degree of inflammatory changes of the intestinal mucosa in patients with different clinical variants of Clostridium difficile - infection. The highest levels of fecal calprotectin are characteristic of hemorrhagic colitis caused by this microorganism.